Conversion of L-rhamnose into ten of the sixteen 1-and 6-deoxyketohexoses in water with three reagents: D-tagatose-3-epimerase equilibrates C3 epimers of deoxyketoses - Gullapalli, P; Yoshihara, A; Morimoto, K; Rao, D; Akimitsu, K; Jenkinson, S; Fleet, G; Izumori, K (2010)
The efficient isomerization of l-rhamnose [the only cheaply available deoxy hexose] to 1-deoxy-l-psicose, 1-deoxy-d-psicose, 1-deoxy-l-fructose, 1-deoxy-d-fructose, 1-deoxy-l-tagatose, 6-deoxy-l-psicose, 6-deoxy-d-psicose, 6-deoxy-l-fructose, 6-deoxy-d-fructose, and 6-deoxy-l-tagatose is described. The conversion of rhamnose to ten of the sixteen 1- and 6-deoxyketohexoses is accomplished in water in three steps. The range of substrates for d-tagatose-3-epimerase (DTE) is extended to 1- and 6-deoxyketoses. An authentic sample of 6-deoxy-d-psicose is prepared from d-psicose. © 2009 Elsevier Ltd. All rights reserved.